Cooperative Effect of Noncovalent Interactions on Tetrel Bonding in Halogenated Silanes. Issue 5 (1st February 2022) - Khera, Mayank; Goel, Neetu
Abstract: Tetrel bond, a weak noncovalent interaction between the σ‐hole of a Group IV element (silicon in our case) and the cloud of an electronegative element (oxygen in our case) is the focus of this work. The percentage strengthening of tetrel bond has been investigated by optimizing 16 binary complexes of halogenated silane and water of general formula SiXn H4−n −H2 O and 16 ternary complexes, of general formula NaX−SiXn H4−n −H2 O, where X=F, Cl, Br and I and n=1, 2, 3 and 4 at various levels of theory defined within the formalism of density functional theory (DFT). With the addition of NaX, tetrel bond between Si and O in SiXn H4−n −H2 O gets strengthened up to 49 %, owing to cooperativity effect exerted by hydrogen bonding between X and H in the ternary complex NaX−SiXn H4−n −H2 O. In the series of complexes studied here, overall stabilization due to cooperativity lies between 10 kJ/mol to 170 kJ/mol. This large extent of reinforcement due to cooperativity has never been showcased before. The exceptional stabilization and reinforcement owe its genesis to the transformation of the ternary complex into a cluster orchestrated by the H‐bonding in most of the cases and covalent bonding in few of the cases. Abstract : Percentage shortening in tetrel bond length with respect to ternary complex and the cooperativity of tetrel bonding and electrostatic interaction.